PEMBELAJARAN BAHASA ARAB MAHARAH QIRA’AH MELALUI PENDEKATAN SAINTIFIK - Ahmad Rathomi (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2019)
AbstractTalking about innovation will never be finished. Innovations are often carried out both in person, institutions and even at the national level policy stage. The change in the national education curriculum from KTSP to the 2013 Curriculum is a form of innovation in the world of national education. The Ministry of National Education certainly hopes that all formal education practitioners in schools can adopt the 2013 curriculum innovation. Practically, this policy raises problems for teachers, namely implementing the 2013 curriculum which one of the characteristics is learning activities based on the scientific approach. Problems with the implementation of the 2013 curriculum also have an impact on learning Arabic. Therefore, this paper attempts to describe the learning activities of Arabic, especially on the topic of reading skills, through a scientific approach. Keywords: Learning; Scientific Approach; Reading Skills. AbstrakBerbicara tentang inovasi seakan tidak akan pernah selesai. Inovasi sering dilakukan baik secara personal, lembaga bahkan sampai pada tahap kebijakan dengan skala nasional. Perubahan kurikulum pendidikan nasional dari KTSP menjadi Kurikulum 2013 merupakan bentuk inovasi dalam dunia pendidikan berskala nasional. Kementerian pendidikan nasional tentunya berharap seluruh praktisi pendidikan formal di sekolah-sekolah dapat mengadopsi inovasi kurikulum 2013. Secara praktis, kebijakan ini menimbulkan permasalahan bagi guru, yaitu mengimplementasikan kurikulum 2013 yang salah satu karakteristiknya adalah kegiatan pembelajaran berdasarkan pendekatan saintifik. Permasalahan penerapan kurikulum 2013 juga berdampak pada pembelajaran bahasa Arab. Maka dari itu, tulisan ini berusaha untuk mendeskripsikan kegiatan pembelajaran bahasa Arab, khususnya pada maharah qira’ah, melalui pendekatan saintifik. Kata Kunci: Pembelajaran; Pendekatan Saintifik; Maharah Qira’ah.